Electronic Attendance with Android-Based QR Code at STMIK Pringsewu to Improve Student and Lecturer Discipline in Lectures - Ida Ayu Putu Anggie Sinthiya; Keni Puspita Sari; Muhamad Muslihudin; Suhendra Suhendra (Tech-E, 2021)
Technology can be used in various fields. One of them is in the field of Education. In this case, it can be done to process databases, and process academic information data, for example: lecture systems, assessment systems, curriculum information, education management or learning materials. It can also implement the system gradually starting from a smaller scope to expanding, making it easier to manage the use of IT in the process of providing education. Electronic Attendance with an Android-based QR code is an application which is able to read the QR code from each user or student scanned by the lecturer in the attendance list process for a course. The development of the Electronic Attendance system with QR code based on Android uses the Software Development Life Cycle (SDLC) system and is described by the Data Flow Diagram (DFD), Entity Relationship Diagram (ERD) and Flowchart models followed by web design using Hypertext Preprocessor (PHP) programming, and My Structured Query Language (MySQL), Javascript, and Cascading Style Sheet (CSS) which produces responsive websites and is converted with android studio into applications